The New handy English-Filipino dictionary - Castillo, Fely S. (Booklore Pub., 2004)
It includes English words and terminologies with their corresponding parts of speech and their equivalent meanings in Filipino. It would be useful to the public as well as to the media practitioners, writers, researchers, teachers and students majoring in Filipino which is the national language of the country.